2004
DOI: 10.1159/000076645
|View full text |Cite
|
Sign up to set email alerts
|

Heat Shock Preconditioning and Eicosanoid Pathways Modulate Caspase 3-Like Activity in Superficially Injured Isolated Guinea Pig Gastric Mucosa

Abstract: Background: After superficial mucosal injury, the disturbed gastric epithelial continuity is restored by cellular migration. Caspase-3 is an enzyme responsible for the execution of stress-induced apoptosis. Interestingly, heat shock proteins (Hsp) including Hsp60 are capable of modulating caspase-3 activity. Interestingly, we have demonstrated that heat shock preconditioning upregulates Hsp synthesis and inhibits restitution and cell proliferation via mechanisms related to de novo protein synthesis and eicosan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 41 publications
1
11
0
Order By: Relevance
“…Superimposed on the augmentation of HSP60 expression in the RVLM during both phases of Mev intoxication was a progressive decline in mitochondrial or elevation in cytosolic HSP60 in the ventrolateral medulla. We reason that this re-distribution of HSP60 may arise from a higher cytosolic presence of the newly synthesized HSP60 (73) or as a result of mitochondrial to cytosolic translocation (31). More importantly, our novel results implicate that the re-distributed HSP60 in the RVLM exerts its anti-apoptotic action by an enhanced interaction between HSP60 and mitochondrial or cytosolic Bax or Bcl-2.…”
Section: Hsp60 Also Interacts With the Bax/bcl-2/cytochrome C/caspasementioning
confidence: 63%
“…Superimposed on the augmentation of HSP60 expression in the RVLM during both phases of Mev intoxication was a progressive decline in mitochondrial or elevation in cytosolic HSP60 in the ventrolateral medulla. We reason that this re-distribution of HSP60 may arise from a higher cytosolic presence of the newly synthesized HSP60 (73) or as a result of mitochondrial to cytosolic translocation (31). More importantly, our novel results implicate that the re-distributed HSP60 in the RVLM exerts its anti-apoptotic action by an enhanced interaction between HSP60 and mitochondrial or cytosolic Bax or Bcl-2.…”
Section: Hsp60 Also Interacts With the Bax/bcl-2/cytochrome C/caspasementioning
confidence: 63%
“…Among the steps shown to be involved in the mechanism of ischemic PC are poly(ADP-ribose) polymerase (PARP) inhibition (Liaudet et al, 2001), caspase-3 activation (McLaughlin et al, 2003), and PARP-1 cleavage by caspase-3 (Garnier et al, 2003). In addition, heat shock protein 70 (HSP70), which regulates apoptotic cell death (Beere et al, 2000;Saleh et al, 2000;Steel et al, 2004;Stankiewicz et al, 2005), may be involved in ischemic PC (McLaughlin et al, 2003;Oksala et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…HSPs protect against ethanol-induced deep, ulcerative gastric injury [4][5][6]. Previously in in vitro models, we have shown that heat shock preconditioning leads to accumulation of HSPs without histologic injury or induction of apoptosis and is accompanied by a reversible increase of electrophysiologic resistance [7][8][9][10]. Interestingly, we have demonstrated that heat shock preconditioning exerts a general inhibition on restitution and proliferation after superficial injury by a mechanism that involves eicosanoid pathways and protein synthesis [7][8][9].…”
Section: Introductionmentioning
confidence: 89%
“…The experiments were performed as described previously [7][8][9][10]. Two halves of fundic mucosae from guinea pigs (n = 50) were mounted in Ussing-chambers and perfused (37 • C) in vitro.…”
Section: Perfusion Of Gastric Mucosa and Heat Shock Preconditioningmentioning
confidence: 99%
See 1 more Smart Citation